Adaptive solar modulation of thermochromic VO2 toward high-performance energy-efficient smart windows - Ke, Yujie (2019)
Smart windows are promised with a significant contribution to the economization of building energy consumption. Such windows can dynamically modulate the indoor solar irradiation, leading to energy-saving for architectural heating and cooling systems. Development of smart windows can mainly be categorized as electro-, thermo-, and photo-stimulated optical response changes. Among them, thermochromic smart windows that change the optical properties in responsive to the temperature are highly competitive due to the low cost, passivity, and rational stimulus-response.